Zinc in human biology - Mills, C. F. (ILSI human nutrition reviews., 1989)
Zinc in Human Biology describes the functions of zinc in the maintenance of health, physiological development and growth. It highlights the importance of factors which govern the utilization of dietary zinc and thus influence susceptibility to zinc deficiency. Of particular note are its critical reviews of controversial reports on the epidemiological significance of zinc. Emphasis is also given to the practical difficulty of achieving an unequivocal diagnosis of zinc deficiency when susceptibility is influenced strongly by environmental and nutritional factors which aggravate or ameliorate clinical responses.